Michelangelo infinito - Lagani, Cosetta ca. 20. Jh; Curallo, Matteo 1976- (Luckyred homevideo, 2019)
"A painter recounts the life of Michelangelo." [imdb.com]
Original: Italien, Vatikanstadt 2018
Bildformat 1.85:1 (16:9)
extra: dietro le quinte ; intervista a Enrico Lo Verso ; trailer
Keywords: Film; DVD-Video